Ortaöğretim coğrafya derslerinde çağdaş ders denetim kriterleri - Yokuş, Aykut (My University, 2024)
Araştırmamızın amacı Milli Eğitim Bakanlığına bağlı ortaöğretim kurumlarında zorunlu olarak okutulan coğrafya dersindeki ders içi denetim uygulamalarının, çağdaş ders denetim modellerine göre uyumunu değerlendirmek ve bununla birlikte çağdaş denetim modellerinden biri olan klinik ders denetim modelinin coğrafya dersinde uygulamalı olarak sonuçlarını ortaya koyabilmektir. Bu amaç için coğrafya öğretmenlerinin, ders denetimlerini gerçekleştiren okul müdürlerinin ve tarafımızca yürütülmüş olan klinik ders gözlem uygulamasına katılan coğrafya öğretmenlerinin görüşlerine başvurulmuştur. Araştırmamız nitel araştırma yöntemlerinden olan olgu bilim deseni ile ortaya konulmuştur. Araştırmamızın üç ayrı çalışma grubu bulunmaktadır. Birinci çalışma grubu, Arnavutköy ilçesinde resmi ve özel okullarda görev yapan seçkisiz örneklem yöntemi ve gönüllük esasına dayalı belirlenen 20 coğrafya öğretmeni oluşturmaktadır. İkinci çalışma grubu, Arnavutköy, Sultangazi ve Başakşehir ilçelerinde resmi kurumlarda görev yapan amaçlı örneklem yöntemiyle belirlenen 20 okul müdürü oluşturmuştur. Son çalışma grubu ise kolayda örneklem yöntemiyle belirlenen klinik ders denetim uygulamasına katılan resmi okullarda görevli 3 coğrafya öğretmeni oluşturmaktadır. Araştırmamızdaki 3 çalışma grubuna da yarı yapılandırılmış görüşme formu uygulanarak veriler elde edilmiştir. Ders içi denetimlerinin en önemli amacı öğretmenin öğretimsel yalnızlığını gidererek ona yol gösterebilmektir. Araştırmamız kapsamında ders denetim öncesi, denetim anı ve denetim sonrasını irdelediğimiz yarı yapılandırılmış görüşme formundaki sorulara okul müdürleri ve öğretmenler çoğu soruda farklı cevap vermişlerdir. Okul müdürleri arasında da ayrıca farklı denetim uygulamalarının olduğu görülmektedir. Araştırmamıza göre bu farklı cevapların ve farklı uygulamaların en temel sebebi ders denetimlerinde uygulama birliğinin olmayışıdır. Uygulama birliğinin sağlanması için ortak bir anlayışla geliştirilen ders içi denetim kılavuzu veya yönergesi hazırlanabilir. Öğretmen dosya ve evrakların incelenmesi, belli kriterler çerçevesinde denetimin yürütülmesi, denetim sonrasında geri bildirim yapılması, denetimin amacı ve içeriğinin öğretmenlere açıklanması, denetim sonrasında planlı bir görüşme gerçekleştirilmesi, mesleki ve branşa uygun yönlendirme yapılması, denetim sonrasında süreç görüşmelerine yer verilmesi, öğretmen ile ilgili tutulan verileri denetim sonrasında paylaşılması yönündeki farklı çıkan cevaplar ve uygulamalardan yola çıkarak okul müdürlerinin bu başlıklarda denetim birliği sağlayabilmek için hizmet içi eğitimlere yönlendirilmesi uygun olabilir. Araştırmamız dahilinde öğretmen ve okul müdürü görüşlerinde göze çarpan en ortak nokta, ders denetimlerinin alan bazında öğretmene katkı sunamadığı yönünde olmuştur. Bununla ilgili öğretmenlerin ve okul müdürlerinin cevaplarından yola çıkıldığında konu ile ilgili bir düzenleme beklentisi içinde oldukları söylenebilir. Bu sorun için eğitim bölgeleri içinde branşa bağlı denetim grupları oluşturulabilir. Araştırmamızın son bölümünde ele alınan çağdaş ders denetim yöntemlerinden biri olan klinik ders denetim uygulama sonuçlarına göre katılımcılar bu gözlem sürecinde; genel manada kendilerini daha rahat hissettiklerini, gözlem öncesi, anı ve sonrasında iletişimin sürekli ön planda olmasından dolayı denetim stresi bakımından daha az strese sahip olduklarını, daha az heyecanlandıklarını belirtmişlerdir. Bunun yanında etkileşimin daha yoğun olması ve samimi bir ortamda gözlem oluşmasını, video ders kayıtlarının öğretmenlerle birlikte analiz edilmesini olumlu bulmuşlardır. Katılımcıların verdikleri cevaplara göre uygulayıcı ve öğretmen branşlarının aynı olması mesleki yönden ve alanı bakımından öğretmenlere katkı sağladığı söylenebilir. Klinik ders denetim uygulamasının olumlu sonuçlarına göre diğer çağdaş ders içi denetim yöntemlerinden; kılavuz denetimi, farklılaştırılmış denetim, emsal denetimi, porfolyo denetimi, öğretimsel denetim modelleri gibi denetim modellerinin ilgili yönergelerle açıklanarak yazılı mevzuat kapsamında uygulamaya alınması, hizmet içi eğitimlerle denetleme görevini yürüten kişilerin bu konuda hizmet içi eğitime tabi olması ders denetimlerindeki yöntem çeşitliliğini artırarak denetimlerdeki tek düzeliği azaltabilir.

The aim of our research is to evaluate the compatibility of in-class supervision practices in the geography course, which is compulsory in secondary education institutions affiliated with the Ministry of National Education, with contemporary course supervision models, and to reveal the practical results of the clinical course supervision model, which is one of the contemporary supervision models, in the geography course. For this purpose, the opinions of geography teachers, school principals who carried out course inspections, and geography teachers who participated in the clinical lesson observation practice carried out by us were consulted. Our research was conducted with the phenomenological pattern, which is one of the qualitative research methods. Our research has three separate working groups. The first study group consists of 20 geography teachers working in public and private schools in Arnavutköy district, determined based on random sampling method and volunteering. The second study group consisted of 20 school principals working in official institutions in Arnavutköy, Sultangazi and Başakşehir districts, determined by the purposeful sampling method. The last study group consists of 3 geography teachers working in public schools who participated in the clinical course supervision application determined by the convenience sampling method. Data was obtained by applying a semi-structured interview form to all 3 study groups in our research.The most important purpose of in-class supervision is to guide the teacher by eliminating his/ her instructional loneliness. Within the scope of our research, school principals and teachers gave different answers to most of the questions in the semi-structured interview form in which we examined the periods before, during and after the course inspection. It is seen that there are different supervision practices among school principals. The main reason for these different answers and different practices is the lack of uniformity of practice in course audits. In-course supervision guide or directive developed with a common understanding can be prepared to ensure unity of application.The most common point that stands out especially in the opinions of teachers and school principals is that course supervision does not contribute to teachers on a field-by-field basis. Based on the answers of teachers and school principals to open-ended questions. it can be said that they expect a regulation. The most important purpose of in-class supervision is to guide the teacher by eliminating his/ her instructional loneliness. Within the scope of our research, school principals and teachers gave different answers to most of the questions in the semi-structured interview form in which we examined the periods before, during and after the course inspection. It is also seen that there are different supervision practices among school principals. According to our research, the main reason for these different answers and different practices is the lack of uniformity of practice in course audits. In order to ensure uniformity of practice, an in-course supervision guide or directive developed with a common understanding can be prepared. Examining teacher files and documents, conducting the audit within the framework of certain criteria, providing feedback after the audit, explaining the purpose and content of the audit to the teachers, holding a planned interview after the audit, providing guidance appropriate to the profession and branch, including process interviews after the audit, keeping records about the teacher. Based on the different answers and practices regarding sharing data after the audit, it may be appropriate to direct school principals to in-service training in order to ensure unity of audit on these topics.According to the results of the clinical course supervision application, which is one of the contemporary course supervision methods discussed in the last part of our research, the participants: In this observation process; They stated that they felt more comfortable in general, had less stress in terms of supervision stress, and were less excited because communication was always at the forefront before, during and after the observation. In addition, they found it positive that the interaction was more intense, observation occurred in a friendly environment, and video lecture recordings were analyzed together with the teachers. According to the answers given by the participants, it can be said that the fact that the practitioner and teacher branches are the same contributes to the teachers in terms of their profession and field. Within the scope of our research, the most common point in the opinions of teachers and school principals was that course inspections did not contribute to teachers on a field-by-field basis. Based on the answers of teachers and school principals, it can be said that they expect a regulation on the subject. For this problem, branch-based supervision groups can be created within education regions. According to the results of the clinical course supervision application, which is one of the contemporary course supervision methods discussed in the last part of our research, the participants during this observation process; They stated that they felt more comfortable in general, had less stress in terms of supervision stress, and were less excited because communication was always at the forefront before, during and after the observation. In addition, they found it positive that the interaction was more intense, observation occurred in a friendly environment, and video lecture recordings were analyzed together with the teachers. According to the answers given by the participants, it can be said that the fact that the practitioner and teacher branches are the same contributes to the teachers in terms of their profession and field. According to the positive results of clinical course supervision application, among other contemporary in-course supervision methods; Supervision models such as guide supervision, differentiated supervision, peer supervision, portfolio supervision, instructional supervision models are explained in relevant guidelines and put into practice within the scope of written legislation, and in-service training and in-service training of people carrying out supervision duties can reduce the uniformity in supervision by increasing the variety of methods in course supervision.
Keywords: Clinical Supervision; Coğrafya; Coğrafya Ders Denetimi; Coğrafya Öğretimi; Contemporary Course Supervision; Course Supervision Criteria; Çağdaş Ders Denetimi; Ders Denetim Kriterleri; Geography; Geography Course Supervision; Geography Teaching; Klinik Denetim; Öğrenim ve öğretim (Orta); Study and teaching (Secondary)